The Role of MRI in Establishing The Optic Nerve in The Orbita Literature Review Study - Novinda Syamantha Djawa; I Made Lana Prasetya; I Wayan Ariec Sugiantara (Lembaga Pengembangan Kinerja Dosen, 2024)
Diagnosing optic nerve disorders in the orbit is a clinical challenge that requires sophisticated imaging technology. MRI has become one of the main diagnostic tools in identifying various optic nerve pathologies, such as Optic Neuritis, Multiple Sclerosis, and tumors. However, it is important to understand in more depth how MRI can play an effective role in this diagnosis process. This study aims to explore the role of MRI in diagnosing optic nerve disorders in the orbit, specifically focusing on Optic Neuritis. This research uses a Literature Review Study approach by collecting data from various sources, including Pubmed, Google Scholar, and online repositories. Relevant data was selected based on established inclusion criteria, and then analyzed to understand the contribution of MRI in the process of diagnosing optic nerve disorders. The results of the study show that the use of ADC values has proven effective in diagnosing Multiple Sclerosis of the optic nerve, while the diagnosis of Optic Neuritis can be made without the use of contrast media with high sensitivity. Imaging techniques with diffusion weighting, fat saturation, and phase oversampling have also been proven to improve the quality of Orbital MRI images by reducing artifacts. It is also recommended to use slice thicknesses of 1 mm, 2 mm, and 3 mm to optimally display small anatomy and pathology. The rFOV-EPI imaging technique is recommended because it can provide high spatial resolution. Thus, through the application of the various MRI imaging techniques and parameters mentioned above, a more accurate and detailed diagnosis can be made regarding the pathological condition of the optic nerve in the orbit. This research makes an important contribution to our understanding of the role of MRI in the diagnosis and management of optic nerve disorders, as well as providing practical guidance for medical practitioners in the clinical use of this technology.